Pengaruh Komitmen Organisasi dan Organizational Citizenship Behavior Terhadap Kepuasan Kerja Pegawai - Aghnia, Siva Asyah; Sunarsi, Denok (Lensa Ilmiah: Jurnal Manajemen dan Sumberdaya, 2023)
This study aims to determine the effect of organizational commitment and Organizational Citizenship Behavior (OCB) on employee job satisfaction at the Special Class 1A Tangerang District Court. The analytical methods used in this study are descriptive analysis, validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation coefficient analysis, determination coefficient analysis, t test and F test. With a total sampling of 67 respondents. The results showed the results of a multiple linear regression equation of 10.927 + 0.366X1 + 0.830X2, meaning that job satisfaction even without being influenced by organizational commitment and OCB had an influence of 10.927. The result of this study is based on the value of the correlation coefficient (R) of 0.923 where the value (R) is between the value of the coefficient interval of 0.80-1.000. This means that the effect of the relationship between the variables of Organizational Commitment and OCB on Job Satisfaction simultaneously is very strong. The population in this study is employees of the Special Class 1A Tangerang District Court.